Probing Factors Shaping Childhood Vaccination of Under-5: A Rural Health Center Perspective - Aparna Sharma; Shambhavee Singh; Vikram Singh; Priya Arora; Kritika; Suruchi Mishra (Journal of Medical Academics)
Introduction: Childhood immunization, a fundamental pillar of public health, has faced renewed challenges in the aftermath of the COVID-19 pandemic. The impact on vaccination coverage, particularly in rural India, prompts an in-depth investigation of factors playing a pivotal role. Aims and objectives: To comprehensively understand the vaccination coverage and its determinants influencing routine immunization practices among under-5 children at a Rural Health and Training Center (RHTC) in Delhi. Methods: This was a descriptive cross-sectional study conducted in the immunization clinic of RHTC Najafgarh. A criterion-based purposive sampling technique was used. A total of 140 mothers or female legal guardians were personally interviewed using a predesigned, pretested semistructured and partially open-ended questionnaire. Results: Vaccination coverage rates were high for most vaccines: 98.6% for Bacillus Calmette–Guérin (BCG), 92.6% for hepatitis B, and 94.9% for oral polio vaccine (OPV) 0. Education level of mothers, familiarity with the recommended immunization schedule, and mothers considering vaccination important were found to be significantly associated with complete vaccination for age (p = 0.030, 0.042, and 0.05, respectively). Focusing on mothers’ perspectives on vaccination, 99.3% of mothers believed that children should be immunized, 73.6% learned about the next dose of vaccination from healthcare workers, and 90% believed it is important to vaccinate according to the schedule. Conclusion: Enhancing maternal education, addressing logistical challenges, and reinforcing the importance of completing the full vaccination schedule through targeted educational campaigns could further improve vaccination rates.